Nycthemeral rhythms of total locomotor activity and oxidative markers in horse - Piccione, Giuseppe; Giannetto, Claudia; Casella, Stefania; Marafioti, Simona; Messina, Vanessa; Assenza, Anna; Faggio, Caterina; Fazio, Francesco (Journal of Applied Biomedicine, 2011)
The aim of this study was to investigate the nycthemeral rhythm of total locomotor activity (TLA) in horse and the possible involvement of the daily organization of rest/activity cycles in the fluctuation of the redox state. For this purpose we recorded TLA and determined oxidative markers in ten clinically healthy Italian Saddle horses. TLA was continuously recorded by means of an actigraphy-based data logger Actiwatch-Mini®. For the assessment of free radicals (dROMs), the antioxidant barrier (Oxy-ads) and the thiol-antioxydant barrier (SHp), blood samples were collected every 4 hours over a 48 h period. One-way repeated measures analysis of variance (ANOVA) showed a statistically significant effect of time of day on all studied parameters. The application of the periodic model and the statistical analysis of cosinor indicate, in horses, the existence of a daily rhythm of the studied parameters during the 48 h of monitoring of the horses. The results show that nycthemeral rhythms of TLA and oxidative markers have different trends in horse. dROMs and Oxy-ads showed a nycthemeral rhythm with an acrophase in the middle of the photophase, and an acrophase of SHp nycthemeral rhythm preceded them. In contrast, TLA showed its acrophase only after the middle of the photophase. TLA showed a lower robustness of rhythms (16.3 and 20.3%) and in respect to the robustness values of the rhythms of oxidative markers (67.3-86.2%). In conclusion, the results of the present investigation showed that oxidative markers have different patterns than locomotor activity, and further studies could be necessary to determine whether other external stimuli, such as solar radiation, food administration or physical exercise are able to influence redox state rhythms in this species.
Keywords: oxidační stres; antioxidancia; periodicita; statistika jako téma; experimenty na zvířatech; Periodicity; cirkadiánní rytmus; Circadian Rhythm; Animal Experimentation; Animals; Antioxidants; Free Radicals; zvířata; pohybová aktivita; Motor Activity; koně; volné radikály; Oxidative Stress; Statistics as Topic; Horses